LEGAL CERTAINTY OF GROSS NEGLIGENCE AS AN ELEMENT OF CRIMINAL LIABILITY FOR MEDICAL PROFESSIONALS: PROBLEMS AND IMPLICATIONS - Darma, I Made Wirya (Faculty of Law, Universitas Pekalongan, 2024)
The legal certainty regarding the requirement of gross negligence as one of the elements of criminalization for medical personnel has become a debated issue due to the absence of clear boundaries in the laws and regulations, resulting in difficulties for judges in determining the criteria for gross negligence and potentially leading to legal uncertainty and injustice. This research aims to analyze the legal certainty regarding the requirement of gross negligence as one of the elements of criminalization for medical personnel in the applicable laws and regulations in Indonesia, as well as to examine the implications of this legal uncertainty on law enforcement and public trust in the medical profession. This research utilizes a normative legal research method with a statutory and conceptual approach, and collects data through library research on relevant primary, secondary, and tertiary legal materials. The analysis is carried out using content analysis techniques and legal interpretation. The research results reveal that the legal certainty regarding the requirement of gross negligence as one of the elements of criminalization for medical personnel is still unclear in the applicable laws and regulations in Indonesia. The lack of a clear definition and criteria regarding gross negligence in the Criminal Code and the Health Law leads to legal uncertainty and difficulties for judges in determining whether a case can be categorized as gross negligence, which has the potential to cause disparities in court decisions. This condition has significant implications for fair and consistent law enforcement, public trust in the medical profession, and the evidentiary process, which becomes more difficult. Therefore, efforts are needed to clarify the legal certainty regarding the requirement of gross negligence to ensure justice and legal certainty for all parties.